(untitled) (Journal of the College of Basic Education, 2023)
1 By examining the sources on the topic of using training systems for research fromThe subject of high sports levels and records, we found that several systems are in accordance withThe data of scientific subjects such as physics, chemistry, statistics, mechanics, and learning are relateddirectly in these systems for different types of ground activities. Obtaining is requiredHigh mathematical levels Working with young men and women to determine athletic achievement.training young people for high levels, in addition to relying on previous sciences, we must determineVarious training systems and games, and among these systems is the high level training system.for young people, and this will open a wide field for research in the multiple fields of variousSports systems Many have engaged in the field of authorship in training and dealt with itMany trends in the field of training in the applied field to increase athletic achievement in the field ofMiracles in Field Capabilities Today, the world is making rapid progress in sporting achievement.It appears in digital events as well as in non-digital events, as we see in tournaments.International, Olympic, international and others.21 research problem:Sports training effectively helps in the development of physical and technical capabilities.tactical, intellectual and mental preparation, and at the same time has an educational effect on the personalityIt is not possible to separate the education of the athlete from habits, ambition, order and respect.And the desire for intellectual and mental preparation through perception, imagination and creativity using